Problemy codziennego funkcjonowania psychospołecznego w związku z dietą bezglutenową w narracji autobiograficznej osoby z celiakią ‒ studium przypadku - Pietras-Mrozicka, Małgorzata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The acceptance of a chronic disease on the example of Coeliac Disease (CD) and its only form of treatment with a gluten free diet (GFD) is a long lasting process which entails distinct emotional states. By disturbing the biography, the illness obliges to transform previous everyday rituals, because of the dietary restrictions. In effect, CD sufferers experience worsening of the health-related quality of life, reluctance to the diet adherence and avoidance of active social life participation. The paper presents the analysis of the subjective way CD and GFD are experienced. The studies are based on the data gathered in an in-depth biographical interview. The focus is on the way the illness becomes a part of the biography, modifying psychosocial functioning. The everyday life of people adhering to a GFD, when compared to the life before the diagnosis, is affected among others, by the loss of freedom of choice, practical constraints within the family life, narrowing of social nets and withdrawal from previous activities. The way they perceive the illness is reflected in the strategies they use to deal with it and the extent to which CD affects their life satisfaction. The negative assessment of the new reality is the source of difficult emotional states, while its acceptance and positive reinterpretation of CD favour better psychosocial functioning and health
Keywords: dietary restrictions; chronic disease; coeliac disease; quality of life; psychosocial functioning; biography